Soil Security for Ecosystem Management Mediterranean Soil Ecosystems 1 - Kapur, Selim.; Kapur, Selim.; Erşahin, Sabit.; Erşahin, Sabit. (Mediterranean Studies, 2014)
The term "Soil Security" is used in the context of maintaining the quality and quantity of soil needed in order to ensure continuous supplies of food and fresh water for our society. Topics in this unique book on the management of soil sustainability in the Mediterranean region include: soil information, land degradation, land desertification, pedoenvironments, and the carbon cycle and sequestration. One main focus of the book is the description of new approaches that have been adapted with regards to interdisciplinary soil ecosystem management to combat and mitigate desertification. The contributing authors are renowned experts in their fields which cover the subjects on traditional as well as innovative land use and management.